A brief analysis of food practices and food taboos on women health in Andhra Pradesh, India - Konduru, Delliswararao; Kundargi, Rajesh Gururaj (International Journal Of Community Medicine And Public Health, 2019)
Background: The cultural beliefs, food taboos play a key role on women and child health in India. Those food practices and taboos directly impact on women and children health. Moreover, these are one of the causes for malnutrition in women and child; sometimes it also leads to death. Methods: The methodology of this study is qualitative study. The primary data collected in Srikakulam and Visakhapatnam districts of Andhra Pradesh, through in-depth-interviews with the help of semi structured interview guides. The selection of the informants is based on simple random selection. Results: All informants are women and they all are home makers only. They not do participant any income generation activities. Seventy five percentages (75%) of the informants are lives in below poverty line, and twenty five percentages (25%) of women are in above poverty line. Conclusions: The cultural beliefs and practices play a role in the distribution of nutrition messages to the community. Those beliefs are affecting to the pregnant women and on their infants. It’s also affects to the community. Many of these beliefs and practices have been passed down for generations.